Bed parallel slip and paleostress analysis of the Kodki fault zone, Kachchh, Western India - Girish Ch Kothyari; Chirag Jani; Sudhanshu Bajpai; Abhishek Lakhote; Gaurav Chauhan; Kamal Agrawal; Rakesh Dumka; Abhishek Shukla; Raj Sunil Kandregula; B. Sairam; Mahesh Thakkar (Quaternary Science Advances, 2024)
The Kodki fault zone comprises a unique fault system along the Median High (MH) zone in the Kachchh Mainland Uplift (KMU) region of the Kachchh Rift Basin (KRB). The structural and paleostress investigation of the Kodki fault zone shows a typical style of bed-parallel slip (BPS) due to repeated reactivation of the normal faults. The fault growth is accompanied by the reactivation of one or both of the fault segments followed by offset due to BSP. In sections where both fault planes reactivate, and propagate past one other forms a bulk between coinciding fault segments that display typical characterization of relay zones. These structures in the Kodki fault section differ from the conventional relay zone in the strata. The thickness of BPS surfaces along the strata equals the fault's throw at the time of the BPS event. Geometrical restoration of the Mesozoic cross-sections exposed across the selected fault displays repeated BPS forming a complex intersecting structure along the Kodki fault zone. Further, the paleostress analysis determines E-W to WNW-ESE maximum extensional stress inhibits recurrences from the reactivation of faults with the MH zone.